2016
DOI: 10.1155/2016/3704289
|View full text |Cite
|
Sign up to set email alerts
|

People Centered Innovation: Enabling Lean Integrated Project Delivery and Disrupting the Construction Industry for a More Sustainable Future

Abstract: People-centered innovation is a paradigm shift in the construction industry. It is derived from the supposition that people not methods, schedules, or budgets deliver projects. Our data suggest that a multilevel, multidisciplinary project team through shared vision, values, and a common vernacular defines, designs, and delivers more successful projects than traditional methods. These projects meet the needs of shareholders, the community, stakeholders, and the planet. We employ the concepts of emotional intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In other words, PDM 4.0 represents features of a project delivery method that answer the demands of the modern construction industry. This version constitutes of digitally integrated, people-centered innovation and sustainability-focused delivery methods [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, PDM 4.0 represents features of a project delivery method that answer the demands of the modern construction industry. This version constitutes of digitally integrated, people-centered innovation and sustainability-focused delivery methods [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (2015) identified how communication behaviours in inter-organisational teams affect innovation. Paolillo et al (2016) explored the procedural and social elements of a large commercial construction project utilising people-centred innovation (PCI). Pishdad-Bozorgi and Beliveau (2016b) analysed the relationship between trust and IPD and offers analysis on how trust-building attributes are supported and leveraged by IPD (Pishdad-Bozorgi & Beliveau, 2016a).…”
Section: Integrated Project Deliverymentioning
confidence: 99%
“…Relational teams do not forsake contracts, but the methods for developing them and the demands of each party throughout the duration of the contract are different. "[T]eam cohesion" developed during the project definition phase "creates a relational climate of trust that is codified in the contractual requirements" (Paolillo et al 2016). Contracts that underpin relational teams consider the long-term implications of the project and its outcomes.…”
Section: Relational Team Approachmentioning
confidence: 99%
“…In a recently published study based on the Akron Children's Hospital project, the authors introduced the concept of upcycle construction capital (Paolillo et al 2016). Upcycle construction capital is defined as the collateral benefits produced by a building project over time.…”
Section: Bambino Stickersmentioning
confidence: 99%
See 1 more Smart Citation